Mengkaji Ruang Publik dari Perspektif Kuasa: Fenomena Kemenangan Aktor Hegemonik Melalui Dominasi Budaya - Arditama, Erisandi (Jurnal Politik Indonesia: Indonesian Political Science Review, 2016)
Public sphere is not an open space without power, but intersection of various actors with their interest. Therefore, by taking study on meronda activity in gardu, this article discusses how power works in public sphere. Gramsci notion on hegemony is used to analyze existing power relation. As closing session, this article claims that efforts to affecting public opinion through culture domination becomes the basis of hegemonic actor victory in influencing power in gardu as pubic sphere.